La reconstruction du village témoin du Bosquel dans la Somme après 1940. Récit, ambitions et paradoxes d’une opération singulière - Xavier Dousson (In Situ)
On 7th June 1940, the village of Bosquel was almost entirely destroyed by the advancing German army. The tabula rasa caused by the war meant that their Town Planner, Paul Dufournet, and his project architects were able to completely redefine the structuring of the village, particularly the placement of its key functions, its inclusion in the rural area, as well as the character and form of its houses and farms. Regarding this last point, the Quesnel farm, the first one completed, became a model for the reconstruction of Bosquel as a whole making a complete break with the former farms of Picardy, and appears as the most singular figure in this reconstruction.